Intolerance and discrimination - Habermas, Jürgen (2015)
This article traces back to the origins of tolerance as a pragmatic politic of the absolutist onarchy through its transformation into an indispensable tool for the establishment of religious pluralism in a democracy. The author makes a distinction between the mere olerance to displaced people, considered lower, and the tolerance based on mutual recognition and mutual acceptance of visions of divergent worlds. This last type of tolerance allows religions and democracy to live together in a plural ambient and opens the way for the reconciliation between multiculturalism and equality.